If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(3x + -9) + 5x = -10 Reorder the terms: -2(-9 + 3x) + 5x = -10 (-9 * -2 + 3x * -2) + 5x = -10 (18 + -6x) + 5x = -10 Combine like terms: -6x + 5x = -1x 18 + -1x = -10 Solving 18 + -1x = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -1x = -10 + -18 Combine like terms: 18 + -18 = 0 0 + -1x = -10 + -18 -1x = -10 + -18 Combine like terms: -10 + -18 = -28 -1x = -28 Divide each side by '-1'. x = 28 Simplifying x = 28
| (2a-3b+4c)-(-a+3b+4c)= | | 2x^4+3x^3-2x=0 | | 4x^4+20x-2=0 | | (-4)-(-10)= | | 4(3x-2)-2=4(x-2)+14 | | (-12)-(-5)= | | 8k-4k=8 | | 2a+2a=50 | | 5x-9=3x+37 | | 3(4x-6)=22 | | 6x-(2x+6)=18 | | 6x-(2x+6x)=18 | | 3c-2=5c-2 | | 4(3y-2)=15y-(8+3y) | | 5b+3=-7 | | 8x-4=3x+3 | | 3-64+1= | | 206-7x=29x+22 | | 3x^3+24x^2+48x=0 | | 12x^5+36x^7+72x^9=0 | | 0.2+0.2n=0.16 | | n+(n+1)+(n+2)=75 | | 1+-32= | | -2(x+6)+3(3x-2)=3(x-4) | | 8u^2-55u-7=0 | | 5(t-4)-3(t-2)=12 | | 6(t+5)=2(3t+15) | | 4x^2-8x-8=0 | | 4n-2=-14n | | 7(t-5)=4(2t+10) | | 6(x-4)=3(2x+5) | | x^5+2=-10 |